2000
DOI: 10.1016/s0735-1097(99)00584-7
|View full text |Cite
|
Sign up to set email alerts
|

Observed and relative survival after aortic valve replacement

Abstract: Old age was not a risk factor for excess mortality after AVR, whereas atrial fibrillation decreased relative survival substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
246
4
19

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(285 citation statements)
references
References 20 publications
16
246
4
19
Order By: Relevance
“…Other studies with larger patient cohorts evaluating the hospitalmortality after primary isolated SAVR report frequencies ranging from 3.1% for single aortic stenosis to 5.6% for all aortic valve diseases. [23][24][25] Long-term follow up studies provide results of time periods beginning at 1 year reporting a survival of 89% to 15 years 46%. 10,24) Our results revealed that hospital mortality rate decreased after the introduction of TAVI (group I: 4.2%, group II: 1.2%); however, due to the low number of patients who died, this is only a statistical trend.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies with larger patient cohorts evaluating the hospitalmortality after primary isolated SAVR report frequencies ranging from 3.1% for single aortic stenosis to 5.6% for all aortic valve diseases. [23][24][25] Long-term follow up studies provide results of time periods beginning at 1 year reporting a survival of 89% to 15 years 46%. 10,24) Our results revealed that hospital mortality rate decreased after the introduction of TAVI (group I: 4.2%, group II: 1.2%); however, due to the low number of patients who died, this is only a statistical trend.…”
Section: Discussionmentioning
confidence: 99%
“…Это было продемонстрировано в большом Швед-ском регистре, в котором участвовали лица с од-номоментным протезированием АоК и АКШ. Раз-личие в возрасте было представлено следующим образом: 7,2 % -люди младше 50 лет, 30,2 % -от 51 до 60 лет, 41,2 % -от 61 до 70 и 51,2 % паци-ентов были старше 71 года [7]. При обследовании 388 человек (средний возраст -72 года), имеющих кальциноз АоК и прошедших коронарографию, наблюдалась статистически достоверная взаимо-связь между кальцинозом АоК и ИБС.…”
Section: кальциноз аортального клапана и эпидемиология ибсunclassified
“…Numerous observational studies have consistently demonstrated that corrective surgery in symptomatic patients is invariably followed by a subjective improvement in quality of life and a substantial increase in survival rates. In addition, AVR may also provide survival benefit for selected asymptomatic patients, when compared to conservative management [10][11][12][13][14][15][16]. The 2012 update of the ESC/EACTS Guidelines for the management of patients with valvular heart disease also states that aortic valve replacement may be considered for asymptomatic patients with severe aortic stenosis and abnormal response to exercise [17].…”
Section: Treatment Of Valvular Aortic Stenosismentioning
confidence: 99%
“…Mean length of hospital stay was 11 days [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. 30 day-mortality rate was 3.5%.…”
Section: Own Experiencementioning
confidence: 99%